Bibliometric Analysis of Global Trends in Cardiac Rehabilitation for Patients with Acute Coronary Syndrome - Faisol Faisol; Erna Rochmawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cardiac Rehabilitation (CR) is a structured, multidisciplinary program for managing cardiovascular disease that includes education, physical exercise, risk factor modification, and psychosocial support for heart patients, including those who have experienced Acute Coronary Syndrome (ACS). This study aims to analyze global research trends and examine cardiac rehabilitation from 1964 to 2025. A bibliometric analysis was conducted on publications in the Scopus database, The search strategy: in this review was based on the following terms: ‘Cardiac Rehabilitation’ and its alternative keywords (‘Acute Coronary syndrome*’,